Modelling wine tourism experiences - Madeira, A. (2019)
Wine experiences contributed to attracting tourists to the destinations, in particular in Portugal where wine is worldwide renowned. This research aims to understand what drives tourists to visit a destination to live a wine experience and how this experience may improve the image and retain tourists. This model conceptual in its essence was applied in an emergent wine region in Portugal – Lisbon. Data were collected in 16 wineries from a random sample of 314 visitors in an emergent wine region, and structural equation modelling (SEM) was applied. Structural equation modelling was used to test hypotheses and validate the conceptual model. Results show that motivation positively influences the wine experiences, which in turn is explained by the dimensions presented in the study. Furthermore, the wine experience influences image and satisfaction positively and the brand equity negatively. From the managerial perspective, implications are discussed as well as the main limitations, and then suggestions for further research are provided.